2023
DOI: 10.32604/or.2023.030395
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA H19 promotes proliferation in hepatocellular carcinoma cells via H19/miR-107/CDK6 axis

ARCHITTAPON NOKKEAW,
PANNATHON THAMJAMRASSRI,
NAPHAT CHANTARAVISOOT
et al.

Abstract: Hepatocellular carcinoma (HCC) is the leading cause of cancer death worldwide; nevertheless, current therapeutic options are limited or ineffective for many patients. Therefore, elucidation of molecular mechanisms in HCC biology could yield important insights for the intervention of novel therapies. Recently, various studies have reported dysregulation of long non-coding RNAs (lncRNAs) in the initiation and progression of HCC, including H19; however, the biological function of H19 in HCC remains unclear. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Another avenue of exploration may encompass interactions between miRNAs and other cellular proteins. For example, H19 (a long non-coding RNA) and circGPR37B (a circular RNA) have shown promise in reducing the effects of oncogenic miRNAs such as miR-107 and miR-4739, respectively[ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another avenue of exploration may encompass interactions between miRNAs and other cellular proteins. For example, H19 (a long non-coding RNA) and circGPR37B (a circular RNA) have shown promise in reducing the effects of oncogenic miRNAs such as miR-107 and miR-4739, respectively[ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…They exert their effects through a multitude of routes. Examples include promotion of angiogenesis or loss of epithelial cell polarity ( e.g., miR-210 and miR-107), immune evasion ( e.g., miR-93-5p), and through unknown mechanisms ( e.g., miR-4739)[ 8 , 12 , 13 ]. As will be discussed later, many of these miRNAs will have relevant interactions with other proteins as well.…”
Section: Significance Of Mirnasmentioning
confidence: 99%
“…For example, the miR-15 cluster promotes cell cycle arrest by targeting multiple key cell cycle regulators, including CDK1, CDK2, CDK6, cyclin D1, cyclin D3, and cyclin E1 [ 70 , 71 ]. Similarly, CDK6 expression was also found to be repressed by miR-107 [ 72 ].…”
Section: Cell Cycle and Regulatorsmentioning
confidence: 99%
“…Consequently, the identification of treatment targets to elucidate potential carcinogenic mechanisms in HCC and the pursuit of more effective treatments are of paramount importance. To date, several studies have identified genes associated with the carcinogenesis of HCC and relevant regulators that may affect the transcription or translation of these genes [ 10 , 11 ]. However, the underlying molecular mechanisms remain elusive [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%